1998
DOI: 10.1103/physrevlett.80.2201
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-Pinned Solitons in the Two-Dimensional Antiferromagnet Detected by Electron Paramagnetic Resonance

Abstract: It is shown that the introduction of a very small amount of nonmagnetic impurities into the magnetic sites of a classical two-dimensional antiferromagnet creates a new type of static (impuritypinned) soliton that affects the Arrhenius, exp͑2E͞T͒, temperature-dependent electron paramagnetic resonance linewidth by drastically changing the parameter E. Data just above the transition temperature for ͑C 3 H 7 NH 3 ͒ 2 M x Mn 12x Cl 4 confirm the existence of these impurity-pinned solitons.[S0031-9007(98)05498-2] PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
38
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…11) was used to explain the EPR line-width in easy-axis (EA) magnets. [12][13][14][15][16][17][18] The classical example of a localized soliton is BP-solution, which exists in isotropic magnets. The scattering problem for such solitons allows an exact analytical solution because of the scale-and conformal-invariance of the model.…”
Section: Introductionmentioning
confidence: 99%
“…11) was used to explain the EPR line-width in easy-axis (EA) magnets. [12][13][14][15][16][17][18] The classical example of a localized soliton is BP-solution, which exists in isotropic magnets. The scattering problem for such solitons allows an exact analytical solution because of the scale-and conformal-invariance of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these authors [6,7] have also shown that the introduction of a very small amount of nonmagnetic impurities into the magnetic sites of a classical 2D antiferromagnet creates a new type of static (impurity-pinned) soliton that affects the Arrhenius, e −Es/T , temperature-dependent EPR linewidth by drastically changing the parameter E s . Using an approach on a discrete lattice, they considered the spin vacancy located at the soliton center and obtained two different impurity-solitons ( the P-soliton and the I-soliton), which were detected in the layered antiferromagnet (C 3 H 7 NH 3 ) 2 M x Mn l−x Cl 4 through EPR measurements [6,7]. The P-soliton has the same structure of the BV-soliton but without a spin at its center, which results in a vortex singularity at the center.…”
mentioning
confidence: 99%
“…Such a result has leads to the appearance of a new type of soliton whose energy is lower than its counterpart in the absence of the spinless impurity [6,7,8]. This 'more fundamental soliton' has been theoretically [7,8,9,10,11] studied and observed in experiments [6].…”
Section: Introductionmentioning
confidence: 99%
“…[6], for details) while c = 2JSa/h = E j /M j , where M j is the soliton rest mass (for details, see Ref. [19]).…”
Section: Introductionmentioning
confidence: 99%